Expansion into Foreign Markets: A Case of FEMCO Filters Private Limited - Abdeen, Zaheer (2009)
Femco Filters Pvt. Ltd. (FFPL), engaged in the manufacture of hydraulic filters for industrial applications, has seen rapid growth in its domestic market over the last five years and has a vision of replicating its success in international markets as well. In an environment powered by rapid economic development in the BRIC countries (Brazil, Russia, India and China) FFPL is facing stiff competition in its domestic markets by Chinese substitutes. This research has been commissioned by FFPL in order to examine the best possible modes of entry into international markets incorporating the companies current and future vision for growth.